Do Pre-service Teachers Dance with Wolves? Subject-Specific Teacher Professional Development in A Recent Biodiversity Conservation Issue - Büssing, Alexander Georg; Schleper, Maike; Menzel, Susanne (Sustainability, 2018)
Biodiversity conservation issues are adequate topics of Education for Sustainable Development (ESD), as they involve ecological, economic and social aspects. But teaching about these topics often challenges teachers due to high factual complexity but also because of additional affective dimensions. As a consequence, teacher professional development in ESD should address these affective components, to better qualify and motivate teachers to integrate conservation issues into their teaching. To investigate behaviourally relevant factors, we selected the context of natural remigration and conservation of the grey wolf (Canis lupus) in Germany and surveyed 120 pre-service biology teachers (M = 23.2 years, SD = 3.3 years) about contextual factors and their motivation to teach about the issue. Participants reported more positive attitudes, higher enjoyment and an increased perceived behavioural control towards teaching the issue in future teachers when they perceived a smaller psychological distance to the issue and an overall higher motivation to protect the species. As this motivation was grounded in more fundamental personality characteristics like wildlife values and attitudes towards wolves, we discuss the central role of these traits as a basis for transformative learning processes and the necessity of a holistic and subject-specific teacher professional development in ESD.